2023
DOI: 10.1038/s41467-023-36671-1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of tree community structure to forest productivity across a thermal gradient in eastern Asia

Abstract: Despite their fundamental importance the links between forest productivity, diversity and climate remain contentious. We consider whether variation in productivity across climates reflects adjustment among tree species and individuals, or changes in tree community structure. We analysed data from 60 plots of humid old-growth forests spanning mean annual temperatures (MAT) from 2.0 to 26.6 °C. Comparing forests at equivalent aboveground biomass (160 Mg C ha–1), tropical forests ≥24 °C MAT averaged more than dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
2
1
0
Order By: Relevance
“…The positive relationship between AGB and tree species diversity found in suction pumping mining forest stands of the present study was reported by other studies in secondary forests [60,83,84] and old-growth forests [24,58,76,80,85]. Because of forest woody productivity, it is usually positively associated with tree species diversity [85]. Due to the coexistence of functionally different species, this may (1) increase resource partitioning of the environment, (2) enable positive plant-plant interactions and (3) improve growing conditions for establishment and growth of other species [79,83].…”
Section: Effects Of Mining Type Stand Age and Distance From The Fores...supporting
confidence: 92%
See 1 more Smart Citation
“…The positive relationship between AGB and tree species diversity found in suction pumping mining forest stands of the present study was reported by other studies in secondary forests [60,83,84] and old-growth forests [24,58,76,80,85]. Because of forest woody productivity, it is usually positively associated with tree species diversity [85]. Due to the coexistence of functionally different species, this may (1) increase resource partitioning of the environment, (2) enable positive plant-plant interactions and (3) improve growing conditions for establishment and growth of other species [79,83].…”
Section: Effects Of Mining Type Stand Age and Distance From The Fores...supporting
confidence: 92%
“…This supports our results in SEM calculations and could explain why the AGB is higher in suction pumping mining forest stands. The positive relationship between AGB and tree species diversity found in suction pumping mining forest stands of the present study was reported by other studies in secondary forests [60,83,84] and old-growth forests [24,58,76,80,85]. Because of forest woody productivity, it is usually positively associated with tree species diversity [85].…”
Section: Effects Of Mining Type Stand Age and Distance From The Fores...supporting
confidence: 88%
“…It suggests that a taller canopy promotes the species coexistence by producing the heterogeneous local environments under light conditions and moisture availability caused by canopy openings in the emergent and canopy layers (Wright et al 2010). In addition, trees in the understory and the subcanopy layer would contribute to forest productivity more than taller trees in a tropical forest (Kohyama et al 2023). Moreover, species diversity in the understory is a source of potential carbon sources for future large trees.…”
Section: Vertical Patterns Of Agb and Species Diversitymentioning
confidence: 99%